2006
DOI: 10.1253/circj.70.1037
|View full text |Cite
|
Sign up to set email alerts
|

Survival in Thalassaemia Major Patients Prognostic Value of Doppler-Demonstrated Left Ventricular Restrictive Filling Pattern

Abstract: ongestive heart failure is the main cause of death in transfusion-dependent homozygous -thalassaemia (thalassaemia major (TM)) patients. When symptoms of heart failure appear, death usually occurs within 1 year. 1,2 Although cardiac death is the most common cause of death in patients with TM, early markers of cardiac function with prognostic impact on survival have not yet been adequately defined. Deposition of iron in the heart is the major determinant of survival in these patients. 3,4 Left ventricular (LV) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Two long-term observational studies following consecutive patients with TDT showed that survival was significantly improved for patients with better compliance to deferoxamine [28,29]. In the first study (N=257; duration 30 years), Gabutti and Piga found that patients with >70% compliance (58% of patients) had a survival rate of 98% compared with a survival rate of 46% for poorly chelated patients ( p <0.000001) [28].…”
Section: Adherence To Ictmentioning
confidence: 99%
See 1 more Smart Citation
“…Two long-term observational studies following consecutive patients with TDT showed that survival was significantly improved for patients with better compliance to deferoxamine [28,29]. In the first study (N=257; duration 30 years), Gabutti and Piga found that patients with >70% compliance (58% of patients) had a survival rate of 98% compared with a survival rate of 46% for poorly chelated patients ( p <0.000001) [28].…”
Section: Adherence To Ictmentioning
confidence: 99%
“…In the first study (N=257; duration 30 years), Gabutti and Piga found that patients with >70% compliance (58% of patients) had a survival rate of 98% compared with a survival rate of 46% for poorly chelated patients ( p <0.000001) [28]. In the second study (N=45; duration 15 years), Efthimiadis and colleagues found that patients with excellent compliance (20% of patients; ICT 6–7 days/week) had a 15-year cumulative survival of 100% compared with 52% survival for patients with poor compliance (47% of patients; ICT ≤3 days/week; p =0.018) [29]. In an analysis using a Markov model based on multiple data sources, including the observational study from Gabutti and Piga mentioned above, adequate compliance to deferoxamine was associated with a decreased risk of complications, including cardiac disease (60% vs 96%), diabetes (9% vs 54%), hypogonadism (47% vs 81%), and hypothyroidism (14% vs 28%) compared with typical compliance (i.e., compliance observed in clinical practice) [30].…”
Section: Adherence To Ictmentioning
confidence: 99%
“…In one report of 45 patients with 15 years of follow-up, 11 patients died, and restrictive LV filling was predictive of death. 153 …”
Section: Diastolic Function and Compliancementioning
confidence: 99%
“…Thus, the main concern is to detect early markers of cardiac function with prognostic impact on survival. In a previous work we have found that left ventricular (LV) restrictive filling pattern (RFP) is an important predictor of cardiac mortality in 45 asymptomatic transfusion‐dependent patients with TM 4 . The 15‐year cumulative survival rate was 58% in patients with LV RFP and 88% in patients with LV non‐RFP (log‐rank statistic = 6.02, P = 0.014).…”
mentioning
confidence: 93%